Enhancement of lithium-sulfur batteries’ performance with spinel CuFe2O4 and MnFe2O4 additives - Low, Han Rou (Nanyang Technological University, 2020)
Lithium-sulfur battery is explored due to its high theoretical energy density of 2500 W h kg-1 and sulfur’s high theoretical specific capacity of 1675 mA h g-1. However, one of the reasons for not commercializing lithium-sulfur batteries is because of the dissolution of polysulfide intermediates. Dissolution of polysulfides results in the loss of the active materials – sulfur. In order to trap the polysulfides, in this experiment, two spinel ferrites, copper ferrites (CuFe2O4) and manganese ferrites (MnFe2O4) are mixed with sulfur and carbon in the cathodes to adsorb the active materials. Static Polysulfide Adsorption Test has been done and the test has shown that MnFe2O4 has a higher adsorption capability for Li2S6 as compared to CuFe2O4. 7 samples (Control, Cu-3, Cu-5, Cu-10, Mn-3, Mn-5 and Mn-10) are produced with 60wt% of sulfur loading in the cathodes. From battery testing, samples with 3wt% of MnFe2O4 additives and 3wt% of CuFe2O4 additives in the cathodes showed a higher initial specific capacity of 1067 mA h g-1 and 900 mA h g-1 as compared to the Control with an initial specific capacity of 706 mA h g-1. Among the 7 samples, cell with 5wt% of MnFe2O4 has registered the highest specific capacity of 653 mA h g-1 after 200 charge-discharge cycles at 0.5C while cell with 5wt% of CuFe2O4 additives has demonstrated the lowest capacity decay per cycle of 0.1194% after 200 charge-discharge cycles at 0.5C.